Protective potential of klotho protein on diabetic retinopathy: Evidence from clinical and in vitro studies. Issue 1 (20th July 2019) - Ji, Baolan; Wei, Huili; Ding, Yao; Liang, Huimin; Yao, Lu; Wang, Hang; Qu, Hua; Deng, Huacong
Abstract: Aims/Introduction: The purpose of the present study was to observe the relationship between serum α‐klotho (KL) protein level and diabetic retinopathy (DR), and to further examine the effects of KL protein on apoptosis induced by palmitic acid (PA) in human retinal endothelial cells. Materials and Methods: A total of 17 healthy people and 60 type 2 diabetes patients were included. According to the results from fundus fluorescein angiography, the diabetes patients were divided into three subgroups: without DR, non‐proliferative DR and proliferative DR. Serum KL level was measured by enzyme‐linked immunosorbent assay. In vitro, human retinal endothelial cells were exposed to PA with or without KL protein. Apoptosis rates were analyzed by flow cytometry analysis. Apoptotic‐related protein expressions were detected by western blotting analysis. Results: Serum KL level was lower in diabetes patients than that in healthy participants ( P = 0.007), and was gradually decreased among the without DR, non‐proliferative DR and proliferative DR subgroups ( P = 0.045). A logistic regression analysis showed that after adjusting for the other confounding factors, serum KL level was independently and negatively related with DR ( P = 0.049). Furthermore, the increased apoptosis rates induced by PA were inhibited with the addition of KL protein. Consistently, KL protein reversed the expression levels of the increased pro‐apoptotic protein Bax and the decreased anti‐apoptotic protein Bcl‐2 induced by PA. However, the anti‐apoptotic effect of KL protein was attenuated by LY294002 through the phosphatidylinositol 3 kinase‐serine∕threonine kinase pathway. Conclusions: The data suggested that KL protein was probably a potential protective factor against retinopathy in type 2 diabetes patients. Abstract : α‐Klotho plays important vasculoprotective roles. We analyzed the relationship between serum klotho level and diabetic retinopathy by clinical and cell data. The results suggested that klotho protein was probably a potential protective factor against retinopathy in type 2 diabetes patients.